2021
DOI: 10.1186/s12876-021-01612-z
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and risk of non-alcoholic fatty liver disease

Abstract: Background Nutrition is a modifiable risk factor that plays an important role in the prevention or delaying of the onset of non-alcoholic fatty liver disease (NAFLD). Previous studies have focused on NAFLD and individual nutrients, which does not take into account combinations of food that are consumed. Therefore, we aimed to investigate the relationship between major dietary patterns and NAFLD. Methods This case–control study was conducted on 225… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 45 publications
4
39
0
Order By: Relevance
“…A study among adults in Taiwan showed that individuals in the highest quartile of a Western dietary pattern, characterized by animal protein, eggs, refined foods and beverages, oil-cooked foods, and high-sugar foods, were likely to have elevated ALT levels (OR = 1.43, 95% CI: 1.04, 1.97), while individuals consuming the Mediterranean diet were correlated with a reduced risk of having abnormal levels of γ-GT (OR = 0.72, 95% CI: 0.53, 0.97) [11]. In accordance, a previous investigation among Iranian adults found greater odds of having NAFLD in subjects with the highest adherence to a Western dietary pattern (OR = 2.61, 95% CI: 1.41, 4.28); meanwhile, subjects in the highest quartile of a healthy dietary pattern were 41% less likely to have NAFLD after controlling for confounders [12]. Moreover, a previous report also mentioned that the role of sedentary lifestyle or physical inactivity was independent from the progression of liver disease [13].…”
Section: Introductionsupporting
confidence: 85%
“…A study among adults in Taiwan showed that individuals in the highest quartile of a Western dietary pattern, characterized by animal protein, eggs, refined foods and beverages, oil-cooked foods, and high-sugar foods, were likely to have elevated ALT levels (OR = 1.43, 95% CI: 1.04, 1.97), while individuals consuming the Mediterranean diet were correlated with a reduced risk of having abnormal levels of γ-GT (OR = 0.72, 95% CI: 0.53, 0.97) [11]. In accordance, a previous investigation among Iranian adults found greater odds of having NAFLD in subjects with the highest adherence to a Western dietary pattern (OR = 2.61, 95% CI: 1.41, 4.28); meanwhile, subjects in the highest quartile of a healthy dietary pattern were 41% less likely to have NAFLD after controlling for confounders [12]. Moreover, a previous report also mentioned that the role of sedentary lifestyle or physical inactivity was independent from the progression of liver disease [13].…”
Section: Introductionsupporting
confidence: 85%
“…Similarly, dietary patterns containing high levels of red meat and refined grains, as well as high-fat dairy and processed foods, could significantly increase NAFLD by 50% [ 29 ]. Saturated fatty acids (SFA) and trans-fatty acids (FA) possibly influence steatosis of hepatic cells by chylomicron intake after consumption of fatty foods [ 44 ]. It is worth noting that a recent study in NAFLD patients demonstrated that the heterocyclic amines (HCAs) produced by high temperatures for an extended period of cooking meat, were associated with IR and were found to be hazardous to health [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of doing physical activity and following a Mediterranean diet on NAFLD has been widely studied in recent years [48][49][50][51]. At the same time, the relevance of psychological biomarkers has also been recently proven in NAFLD [24,52].…”
Section: Discussionmentioning
confidence: 99%